A digital game for preserving food cultural heritage: design and evaluation of ThaiFoodAdventure game - Kannattha Chaisriya; Lester Gilbert; Ratchada Suwangerd; Sasithorn Rattanarungrot (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Digital games are a powerful tool for the presentation of food cultural heritage. A digital game was designed and developed to raise and enhance young people’s interest in and knowledge of Thai food cultural heritage, currently an under-researched field. The platform game was played on a mobile device and required the collection of food ingredients appropriate to popular cuisine in four Thai regions while overcoming obstacles. A sample (N=61) of young people (mean age=19 years) played the game, and the differences in their pre and post-test knowledge of and interest in Thai food and its cultural heritage were analyzed. The findings showed a highly significant increase in interest in and knowledge of Thai food cultural heritage, and did so despite the opinion of some participants that learning games were less interesting than conventional games, or that games were not a good way of raising interest in cultural heritage.